2012
DOI: 10.2298/eka1294007h
|View full text |Cite
|
Sign up to set email alerts
|

Size of government and economic growth: A nonlinear analysis

Abstract: The new growth theory establishes, among other things, that government expenditure can manipulate the economic growth of a country. This study attempts to explain whether government expenditure increases or decreases economic growth in the context of Sri Lanka. Results obtained employing a productive output series and applying an analytical framework based on second degree polynomial regression are generally consistent with previous findings: government expenditure and economic growth are positively corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
0
10
1
5
Order By: Relevance
“…In contrast, a positive contribution of public spending to economic growth has also been found in other studies [38]. Meanwhile, a few studies have found public spending to have non-linear effects on economic growth [39]. Interpreting the results of a mixed test, Gemmell et al [24] point out the role of budget constraints in the relationship between public spending and economic growth.…”
Section: Literature Reviewmentioning
confidence: 91%
“…In contrast, a positive contribution of public spending to economic growth has also been found in other studies [38]. Meanwhile, a few studies have found public spending to have non-linear effects on economic growth [39]. Interpreting the results of a mixed test, Gemmell et al [24] point out the role of budget constraints in the relationship between public spending and economic growth.…”
Section: Literature Reviewmentioning
confidence: 91%
“…An experimental study, by16 procurement practitioners in local government in England, shows that failure to save costs is a matter of uneconomical MFM principles (Preuss, 2007). Herath (2012) echoes the sentiment that failure of local government to control finances is directly related to the inefficiencies of MFM. These authors state that spending by local government has a significant relationship with MFM.…”
Section: Objectivesmentioning
confidence: 95%
“…Sri Lanka ekonomisinde optimal kamu harcamaları büyüklüğü yaklaşık %27' dir. Herath (2010Herath ( , 2012' ın çalışmalarını diğer çalışmalardan ayıran belirgin özellik diğer çalışmaların aksine Herath' ın uzun dönem serilerini kullanmasıdır. Herath (2010)…”
Section: Introductionunclassified